2020
DOI: 10.3390/ma13071785
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Adsorption of Sulfamethoxazole from Aqueous Solution by Lignite Activated Coke

Abstract: In this paper, lignite activated coke was used as adsorbent for dynamic column adsorption experiments to remove sulfamethoxazole from aqueous solution. The effects of column height, flow rate, initial concentration, pH and humic acids concentration on the dynamic adsorption penetration curve and mass transfer zone length were investigated. Results showed penetration time would be prolonged significantly by increasing column height, while inhibited by the increasement of initial concentration and flow rate. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, a direct comparison with other MOFcontinuous flow systems is impossible since all the studies reported so far are exclusively based on sorption processes (mainly vapor phase) and not catalytic ones. In an attempt to position our results within the context of EOCs elimination from water, a comparison can be made with the kinetic constants obtained using MOFs or other adsorbent materials (i.e., the adsorption of diazinon using MIL-100(Cr): KTh = 5.11 -8.33 mL•min -1 •mg -1 , 61 sulfamethazole with lignite activated coke: KTh = 0.04 -0.01 mL•mg -1 •min -1 , 68 or atenolol with activated carbon: KTh = 2.28 mL•mg -1 •min -1 ). 69 Finally, although this laboratory scale MOF photoreactor is still far from its application in wastewater treatments, our work presents the very first example of continuous-flow photodegradation of EOCs using MOFs with a considerably good breakthrough time and working under operation conditions on the range of those normally applied in wastewater treatment plants.…”
Section: Sulfamethazine (Smt)mentioning
confidence: 99%
“…However, a direct comparison with other MOFcontinuous flow systems is impossible since all the studies reported so far are exclusively based on sorption processes (mainly vapor phase) and not catalytic ones. In an attempt to position our results within the context of EOCs elimination from water, a comparison can be made with the kinetic constants obtained using MOFs or other adsorbent materials (i.e., the adsorption of diazinon using MIL-100(Cr): KTh = 5.11 -8.33 mL•min -1 •mg -1 , 61 sulfamethazole with lignite activated coke: KTh = 0.04 -0.01 mL•mg -1 •min -1 , 68 or atenolol with activated carbon: KTh = 2.28 mL•mg -1 •min -1 ). 69 Finally, although this laboratory scale MOF photoreactor is still far from its application in wastewater treatments, our work presents the very first example of continuous-flow photodegradation of EOCs using MOFs with a considerably good breakthrough time and working under operation conditions on the range of those normally applied in wastewater treatment plants.…”
Section: Sulfamethazine (Smt)mentioning
confidence: 99%
“…Hence, it is not logical to compare the three models and say that one is better than the other since all three are mathematically equivalent. In that sense, the model comparison analysis presented by Li et al [ 1 ] in their paper has flaws, and their conclusions are not meaningful.…”
Section: Discussionmentioning
confidence: 95%
“…The recent paper titled “Dynamic Adsorption of Sulfamethoxazole from Aqueous Solution by Lignite Activated Coke” published by Li et al [ 1 ] in this journal describes dynamic column adsorption experiments to remove sulfamethoxazole (SMX) using lignite activated carbon. This paper is novel and has useful information in advancing the use of adsorption technology in the removal of emerging pollutants from wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…where τ (min) is the time required for the effluent concentration to be 50% of the influent concentration; C 0 (mg/L) is the nitrate nitrogen concentration in the influent; C t (mg/L) is the nitrate nitrogen concentration in the effluent at time t; t (min) is the running time; and K YN (min −1 ) is the constant of the Yoon-Nelson model [26].…”
Section: Yoon-nelson Modelmentioning
confidence: 99%